Ancient Maya Commerce : Multidisciplinary Research at Chunchucmil - Hutson, Scott; Project Muse. (Boulder : University Press of Colorado, 2017)
Nearly two decades of research at Chunchucmil, Yucatan, Mexico documented a thriving city of 40,000 people without the powerful kings and massive temples seen at other Maya centers. What brought people to this area, the driest in the Maya world, and how did they survive? Ancient Maya Commerce provides a pioneering study in economic anthropology, making the strongest case yet that ancient Maya economies were quite complex, containing markets in addition to other forms of exchange. Multiple lines of evidence including household archaeology, regional survey, paleo-ecology and soil chemistry show that Chunchucmil was a major center for both short and long distance trade, integrating the Guatemalan highlands, the Gulf of Mexico and the interior of the northern Maya lowlands. By placing Chunchucmil into the broader context of emerging research at other Maya cities, this book helps reorient our understanding of ancient Maya economies, foregrounding the increasingly important role of commerce.
Introduction / Scott R. Hutson and Bruce H. Dahlin -- Map of Chunchucmil / Scott Hutson and Aline Magnoni -- Architectural group typology and excavation sampling within Chunchucmil / Scott R. Hutson, Aline Magnoni, Bruce H. Dahlin -- Chunchucmil chronology and site dynamics / Socorro Jimenez, Aline Magnoni, Eugenia Mansell, and Tara Bond-Freeman -- Chunchucmil's urban population / Scott R. Hutson, Aline Magnoni, Traci Ardren, Chelsea Blackmore, and Travis Stanton -- Environmental heterogeneity in the Chunchucmil economic region / David Hixson, Timothy Beach, Sheryl Luzzadder-Beach and Bruce H. Dahlin -- Hydrology on the edge of the Chicxulub Crater : Chunchucmil and Uc-Cansahcab groundwater resources / Sheryl Luzzadder-Beach and Timothy Beach -- Hinterland settlement patterns within the Chunchucmil economic region / David R. Hixson and Daniel E. Mazeau -- Soils and agricultural carrying capacity / Timothy Beach, Sheryl Luzzadder-Beach, Ryan V. Sweetwood, Patrice Farrell, Daniel E. Mazeau, and Richard E. Terry -- Perishable resources produced for exchange in the Chunchucmil economic region / Bruce H. Dahlin, Traci Ardren, David R. Hixson, and Anthony P. Andrews -- Marketing within Chunchucmil / Scott R. Hutson, Richard E. Terry, and Bruce H. Dahlin -- Connections beyond Chunchucmil / Traci Ardren, Scott R. Hutson, David R. Hixson and Justin Lowry -- Conclusion / Scott R. Hutson.
In English.
Description based on print version record.
Keywords: Mayas -- Economic conditions; Mayas -- Commerce; Mayas -- Antiquities; Excavations (Archaeology); Antiquities; SOCIAL SCIENCE -- General; SOCIAL SCIENCE -- general; HISTORY -- Latin America -- Mexico; Archaeology; Humanities; Mayas -- Commerce; Mayas -- Conditions economiques; Mayas -- Antiquites; Fouilles (Archeologie) -- Mexique -- Chunchucmil (Site archeologique); Mayas -- Commerce; Mayas -- Economic conditions; Mayas -- Antiquities; Excavations (Archaeology) -- Mexico -- Chunchucmil Site; Mexico -- Chunchucmil Site; Mexico; Mexique -- Antiquites; Chunchucmil (Mexique : Site archeologique); Mexico -- Antiquities; Chunchucmil Site (Mexico); Electronic books